2006
DOI: 10.1016/j.chembiol.2006.09.017
|View full text |Cite
|
Sign up to set email alerts
|

A Monoselective Sphingosine-1-Phosphate Receptor-1 Agonist Prevents Allograft Rejection in a Stringent Rat Heart Transplantation Model

Abstract: FTY720 is an immunomodulator with demonstrated efficacy in a phase II trial of relapsing multiple sclerosis. FTY720-phosphate, the active metabolite generated upon phosphorylation in vivo, acts as a potent agonist on four of the five known sphingosine-1-phosphate (S1P(1)) receptors. AUY954, an aminocarboxylate analog of FTY720, is a low nanomolar, monoselective agonist of the S1P(1) receptor. Due to its selectivity and pharmacokinetic profile, AUY954 is an excellent pharmacological probe of S1P(1)-dependent ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 35 publications
4
99
1
Order By: Relevance
“…6B). In accordance with documented lymphopenic response induced by S1P 1 -specific agonists (Sanna et al, 2004;Pan et al, 2006), a single intraperitoneal injection of CYM-5442 induced lymphopenia for least 18 h (data not shown). Despite systemic effects on naive lymphocyte recirculation, intratracheal delivery of CYM-5442 for up to 2 mg/kg i.t.…”
Section: T Cell Suppression By S1p Analog Modulation Of Dcs 899mentioning
confidence: 58%
“…6B). In accordance with documented lymphopenic response induced by S1P 1 -specific agonists (Sanna et al, 2004;Pan et al, 2006), a single intraperitoneal injection of CYM-5442 induced lymphopenia for least 18 h (data not shown). Despite systemic effects on naive lymphocyte recirculation, intratracheal delivery of CYM-5442 for up to 2 mg/kg i.t.…”
Section: T Cell Suppression By S1p Analog Modulation Of Dcs 899mentioning
confidence: 58%
“…To test this hypothesis, we have examined the clinical efficacy of a small molecule agonist that specifically targets S1P1 receptor activity (AUY954) in the context of SJL/J relapsing-remitting EAE. AUY954 has previously been shown to prevent acute allograft rejection (11), to modulate allergic responses (12), and to reduce neuroinflammation in acute and chronic settings (13,14). We found that AUY954 treatment ameliorated the clinical symptoms of relapsing-remitting EAE in SJL/J mice, concomitant with reduced appearance of cytokine-producing lymphocytes in the CNS.…”
supporting
confidence: 48%
“…PAR1 antagonist RWJ58259 (5 mg kg -1 ), S1P1/S1P3 agonist AAL(R) (2-amino-4-(4-heptyloxyphenyl)-2-methylbutanol) (0.5 mg kg -1 ) 28 , S1P1 agonist AUY (AUY954) (1 mg kg -1 ) 29 or thrombin inhibitor hirudin (120 mg kg -1 lepirudin, 1 mg kg -1 PEG hirudin) were bolus-injected intravenously. For CLP, mice were anaesthetized (ketamine/xylazine, 100/ 8 mg kg -1 ) to ligate 1 cm of caecum for two punctures (21G needles), confirmed to be patent by extrusion of stool.…”
Section: Methods Summarymentioning
confidence: 99%